Behçet’s disease presenting with Budd–Chiari syndrome and intracardial thrombus: a case report - Kim MJ; Jo YS; Kim JH; Kim YJ; Kim KH; Lee EB; Song YW; Lee EY (International Medical Case Reports Journal, 2011)
Minji Jennifer Kim1, Yong Suk Jo2, Jee Hyun Kim2, Yong-Jin Kim3, Kyung Hwan Kim4, Eun Bong Lee2, Yeong Wook Song2, Eun Young Lee21School of Medicine, University of Manchester, Manchester, UK; 2Division of Rheumatology, 3Division of Cardiology, Department of Internal Medicine, 4Department of Thoracic Surgery, Seoul National University College of Medicine, Seoul, Republic of KoreaAbstract: Budd–Chiari syndrome has been described as a late complication of Behçet’s disease. Although the mortality rate associated with Behçet’s disease is low, it can escalate in the presence of Budd–Chiari syndrome and may be further complicated by intracardial thrombus formation. It is therefore important to detect and initiate management early in the disease course. The imaging modalities of choice should be minimally invasive as certain procedures may aggravate Behçet’s disease by initiating a thrombosis or aggravating an existing one. In Behçet’s disease-induced Budd–Chiari syndrome, cardiac investigation is crucial in the work-up in order to identify any cardiac involvement and determine the etiology of intracardial thrombus. Furthermore, the treatment should ultimately focus on controlling the activity of Behçet’s disease. We report an unusual case of Behçet’s disease presenting with Budd–Chiari syndrome complicated by intracardial thrombus in a young Korean man.Keywords: Behçet’s disease, Budd–Chiari syndrome, intracardial thrombus